The Synagogue as locus of ministry in Luke-Acts : a socio-historical study of Luke 4:16-30 - Silas, Dogara Turrang (Stellenbosch : Stellenbosch University, 2020)
Thesis (PhD)--Stellenbosch University, 2020.